Body Mass Index (BMI) in athletes of a futsal team in times of COVID-19 - Neto. J. T.; Farias da Silva, L. F.; Moraes da Silva, V. T.; Cavalcante Silva, A. K.; Pires de Lima Sandri, M.; Bezerra Santos, D. H. (Acta Scientiae Anatomica, 2021)
INTRODUCTION: The pandemic involving the new coronavirus (COVID-19) has generated major changes in the lifestyle of the world population. In Brazil, to contain the SARS-CoV-2 outbreak, based on the World Health Organization (WHO), the Ministry of Health regulated the isolation criteria that should be applied by the health authorities to the population (Ministry of Health, 2020). One of the publics harmed by the quarantine was the futsal athletes, who in times like this, must maintain the care with habits, so that isolation does not influence the return to face-to-face activities. The body mass index (BMI) is an anthropometric measure used in an international standard, which assesses whether people are malnourished, ideal weight, overweight or with some degree of obesity, through a simple calculation between height (m) and body weight. weight (Kg). Thus, a relation of appropriation of the BMI with futsal athletes in the period of non-presential activities becomes evident. In this sense, we seek to identify the BMI in athletes of a futsal team in times of COVID-19. MATERIALS AND METHODS: The study sample consists of male athletes (n = 28) from a futsal team. To analyze the BMI, in which what is considered normal varies between 18 and 24.9, an online form was used that collected data on anthropometric measurements such as height (m) and weight (Kg), and applied the Free and Informed Consent Term (FICT). After tabulation of data, BMIs were calculated using anthropometric measurements and subsequently, a descriptive analysis of the data was performed using the mean and standard deviation. RESULTS: The mean and standard deviation found are for age (22 ± 5.4), with respect to weight, the athletes had (75.8 kg ± 8.1), the height was (1.77 ± 0.1), and for the BMI (24.2 ± 2.2). The results indicate that the athletes are within the recommended limit for the normal range, referring to the BMI. This indicates that for the evaluation of athletes, more advanced methods of anthropometry are needed, which have low cost, such as the adipometer, which can bring greater visibility, for the present data and the real percentage of fat of this population. CONCLUSION: It is concluded that the vast majority of athletes are in the normal range, related to BMI, without characteristics such as: malnutrition, overweight or obesity.